Laminar Boundary Layer Flow of Non-Newtonian Power Law Fluid past a Porous Flat Plate - JADHAV, Dr. B.P. (Journal of Global Research in Mathematical Archives(JGRMA), 2014)
Laminar boundary layer flow of non-Newtonian Power law fluid past a Porous flat plate has been considered. The governing equations of continuity and momentum are transformed into ordinary differential equations using similarity transformations. The equation is solved by using method of successive approximations starting with zeroth approximation. For n=1 the results tallies with Corresponding results for Newtonian fluids. Velocity profiles are drawn for different values of parameter n, suction/injection parameter shows the behavior of power law fluids. Keywords: - Laminar boundary layer, Power law fluids, successive approximations, velocity profiles, suction /injection.